If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 0.16(y + -6) + 0.02y = 0.08y + -0.7 Reorder the terms: 0.16(-6 + y) + 0.02y = 0.08y + -0.7 (-6 * 0.16 + y * 0.16) + 0.02y = 0.08y + -0.7 (-0.96 + 0.16y) + 0.02y = 0.08y + -0.7 Combine like terms: 0.16y + 0.02y = 0.18y -0.96 + 0.18y = 0.08y + -0.7 Reorder the terms: -0.96 + 0.18y = -0.7 + 0.08y Solving -0.96 + 0.18y = -0.7 + 0.08y Solving for variable 'y'. Move all terms containing y to the left, all other terms to the right. Add '-0.08y' to each side of the equation. -0.96 + 0.18y + -0.08y = -0.7 + 0.08y + -0.08y Combine like terms: 0.18y + -0.08y = 0.1y -0.96 + 0.1y = -0.7 + 0.08y + -0.08y Combine like terms: 0.08y + -0.08y = 0.00 -0.96 + 0.1y = -0.7 + 0.00 -0.96 + 0.1y = -0.7 Add '0.96' to each side of the equation. -0.96 + 0.96 + 0.1y = -0.7 + 0.96 Combine like terms: -0.96 + 0.96 = 0.00 0.00 + 0.1y = -0.7 + 0.96 0.1y = -0.7 + 0.96 Combine like terms: -0.7 + 0.96 = 0.26 0.1y = 0.26 Divide each side by '0.1'. y = 2.6 Simplifying y = 2.6
| 3w+4=2w+11 | | 0.6y+6.5=0.5(9+y) | | 6p=91 | | 6x+5y+2x= | | 28-2x=34 | | (6x)+(4x-3)=46 | | -4.5x+1.1=-16.9 | | 4(2x-8)-7=4(x-4)+5 | | .7x+4.2=.6x+1.4 | | 7x+6x(4)=-93 | | 14x-(6x-3)=59 | | 2(4z+1)-7=59 | | 6[2-(3+4x)]-2x=-8+2(1-13x) | | (2x-2)+(5x-7)= | | X-25/100 | | 2x^2-12x-12= | | 37=29-2(x-1) | | 0.09xX=115.80 | | 8/50= | | w=8s+p | | -16+26=2(x+1) | | .75x+3=x+.5 | | 6/3x-5=3/2x | | 2(x-10)=-8 | | 0.09xX=83.07 | | (-4±√20)/2 | | -9-2x+6x=27 | | 37x+7=6(6x+1) | | 18x-7=14x-23 | | 2x+23y=11 | | y+1.2=2 | | 9x+1.5y=11 |